Greek Textual Archaeology and Erotic Epigraphy in Simeon Solomon and Michael Field - Stefano Evangelista (Cahiers Victoriens et Edouardiens)
This article examines the use of the Greek language as object of desire in works by the painter Simeon Solomon and the poetic duo Michael Field (Katharine Bradley and Edith Cooper). Drawing on archaeology and epigraphy, as well as on more traditional text-based branches of classical studies, Solomon and Michael Field insert Greek words on the canvas and on the page in order to create experimental dialogues between verbal and visual media. In particular, Greek inscriptions and epigraphs work to promote the radical artistic doctrine of art for art’s sake and to reclaim the dignity of same-sex love.